Motivations of Users Participating in MNES’ User Communities - A Comparison between the Indian and Dutch Users in the Application Software Industry - Haimakainen, Eveliina (My University, 2014)
The markets have become more demanding for companies, when they have to bring new products/services to the markets faster. Also, the needs of customers are dispersed and change rapidly. Many companies cannot face these challenges all by themselves, which is why an increase can be seen in open innovation. Open innovation means a company which uses external resources for its innovation. There are many options, one of which is the user communities. These are mediated by the Internet, where users of a company’s products/services come to communicate with each other. This knowledge flow that the discussions consist of is an important innovation source for companies. Managers are challenged by this fairly new way of doing innovation, since they need to understand what motivates users to participate in the communities. With multinational companies, understanding how culture affects these motivations is also crucial. The types of motivations can be roughly divided into extrinsic and intrinsic motivations. Extrinsic motivation include among others pay, which is not important for users. Extrinsic motivations are also found to sometimes be of negative influence. On the other hand intrinsic motivations play a big role in user communities and therefore managers are advised to use them when motivating users. Altogether 24 Indian and Dutch users from Adobe’s and Google’s communities are compared in this study to understand the role of culture has with motivation. Even though these are two very different cultures, the difference between their motivations is not substantial though differences can be found. Especially the factors that influence most and least their motivation to participate are similar across cultures. It is clear, that these shared motivations can only be applied to Internet based environments and more differences could be found in a normal work environment. Nevertheless, managers can use this information to know how to motivate users and not use resources in differentiating the means of doing so in vain.
Keywords: Open innovation; User Community; User; Extrinsic Motivation; Intrinsic Motivation; Culture; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|